PROFIL KEMANDIRIAN BELAJAR MAHASISWA TAHUN PERTAMA - Riska Utami; Siti Fashiha Arifa; Maharani Jasmine Najmi; Nyimas Aisyah Salwaa Humaira; Fadhlina Rozzaqyah (EDU RESEARCH, 2024)
The purpose of this study was to obtain a description of learning independence in first year students of the guidance and counseling study program at Sriwijaya University. Ha; this is motivated by students as individuals who are required to be independent if the independence of students is at a low level, it will have an impact on individuals to experience learning disorders. this study uses total sampling with a population of 87 guidance and counseling students class of 2023 Sriwijaya University. data collection uses a Likert scale with 5 alternative answers, namely often always sometimes rarely and never. this type of research uses descriptive quantitative. Based on the results of research that has been conducted on 2023 guidance and counseling students at Sriwijaya University, it is found that students have learning independence at a moderate level, namely as many as 6 students (7%) with a very high level of learning independence, 21 students (24%) with a high level of learning independence, 30 students (34%) with a moderate level of learning independence, 25 students (29%) with a low level of learning independence, and 5 students (6%) with a very low level of learning independence.